A new species of the genus Podothrips Hood (Thysanoptera; Phlaeothripidae) from Thailand - Minoura, Kazushige; Masumoto, Masami (Zootaxa, 2020)
Podothrips etsukoae sp. n. is described based on specimens collected from bamboo at Bangkok, Thailand.